The transmission dynamics of Lassa fever virus - Ofem*, I.D.; Adagba†, H.O. (International Journal of Mathematical Analysis and Modelling, 2023)
Lassa fever Virus (LFV) is a rare, acute arena viral hemorrhagic fever caused by Lassa virus, which is often fatal if untreated. In this research work, we developed a model that describes the dynamics of Lassa fever Virus (LFV) disease in human population compartments involved with vital dynamics (birth and death rates), incorporating exposed quarantine individuals of 6 to 21days window period and treatment of infected individuals of 21days (+) of infectious period in the trends of infection progression which are influenced by public health education campaign. A system of Nonlinear differential equations was formulated for the transmission dynamic of Lassa fever virus (LFV). The model has the Basic Reproduction Number (Ro) and effective reproductive number (Re), the Stability analysis of the model indicated that the local and global disease-free equilibrium (DFE) is stable and indeed when (Ro) < 1 and unstable when (Ro) > 1. Numerical results show that the infected individuals should be quarantined and given health education campaigns before treatment, because both complement each other in reducing the spread of Lassa fever virus as well as increasing the rate of recovery of the infected individuals.